CULTURAL LIFE IN UZBEKISTAN DURING WORLD WAR II - Tursunboyev, Yahyobek (Educational Research in Universal Sciences, 2023)
ABSTRACT This article delves into the cultural life of Uzbekistan during World War II, examining how the nation’s rich heritage, literature, art, performing arts, and educational pursuits persevered amidst the chaos and devastation of the war. Despite the challenges of the time, Uzbekistan’s diverse cultural tapestry remained a source of comfort and identity for its people. Renowned poets and artists used their talents to inspire and uplift the nation, while theaters and cinemas provided an escape and a means to foster national solidarity. Educational institutions and scholars worked tirelessly to preserve Uzbekistan’s cultural legacy for future generations. This article highlights the indomitable spirit and resilience of the Uzbek people, showcasing the power of culture to unite and thrive even in the face of adversity.